Dietary practice and associated factors among lactating mothers in Dangila District in the Awi Zone Amhara region Ethiopia, 2022: a cross-sectional study - Mulatu, Sileshi; Mulatu, Getasew; Gedif, Azeb (Frontiers in Nutrition, 2025)
IntroductionLactation is the critical time for meeting the nutritional demands of mothers and infants. Mothers from low-income countries, including Ethiopia, are considered nutritionally vulnerable. Good dietary practices for mothers during lactation are therefore important for the good health of their children. The main objective of this study was to assess dietary practice and associated factors of lactating mothers in Dangila Zuria District, Amhara region, Ethiopia, 2022.MethodsA community-based cross-sectional study was conducted among 609 lactating women from March 1st to May 1st 2022. The study participants were selected using a straightforward simple random sampling techniques. Data was collected by using structured questionnaires. The data was entered in Epi-data and exported to SPSS version 23 for analysis. Bi-variable and multi-variable logistic regression analyses were used to see the relevant associations. The variable significantly associated with dietary practice was identified based on a P-value ≤ 0.05.ResultsThis study revealed that only one-third 204 lactating mothers, demonstrated good dietary practices. Notably, several factors were significantly associated with poor dietary practices: mothers with a family size greater than four had 3.01 times higher odds of inadequate dietary habits (AOR = 3.01; 95% CI: 1.56, 9.28), while those with birth intervals of <2 years faced 2.31 times greater odds (AOR = 2.31; 95% CI: 1.49, 3.56). Additionally, daily laborers exhibited a striking 9.35 times higher likelihood of poor dietary practices (AOR = 9.35; 95% CI: 8.02, 19.96), and food-insecure mothers had 4.93 times higher odds of inadequate nutrition (AOR = 4.93; 95% CI: 3.40, 7.16).ConclusionIn conclusion, the dietary practices of lactating mothers were found to be suboptimal, falling below WHO and FAO recommendations. Factors such as family size, birth intervals, maternal occupation (especially daily laborers), and food insecurity were identified as significant contributors. Addressing these issues is crucial. Key stakeholders, including the Ministry of Health (MOH), Regional Health Bureaus (RHB), and health professionals, must work together to alleviate food insecurity, promote optimal family planning, and educate mothers on proper nutrition. Addressing these challenges is essential to achieving global objectives such as reducing malnutrition, improving maternal health, and ensuring healthy child development.